ЖАСЫ ҮЛКЕН – ТӘРБИЯШЫ ҲӘМ ТӘРБИЯ ҚУРАЛЫ СЫПАТЫНДА - Пазылов, А.К. (ILIM hám JÁMIYET, 2019)
It the article the author states that the elders are educators and good sample for the young generation, they can be a means of upbringing and they always should be a sample for them.